The Implementation of the Problem Based Learning in Teaching English at the Second Grade of Pondok Pesantren Ashhabul Yamin Lasi - Yusvendy, Sherly Dwi; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Pusdikra-Publishing.com, 2024)
This research was done to find out the Implementation of Problem Based Learning Model in Teaching English at the second grade of Pesantren Ashhabul Yamin Lasi. This study aims to determine the implementation of the problem based model at the Ashhabul Yamin Lasi Islamic Boarding School.This study aims to 1) To find out how do the teacher implement problem based learning model in teaching english . 2) To find out what are the problem faced by teachers while teaching using the problem based learning model at the Ashhabul Yamin Lasi Islamic Boarding School. This research is a descriptive qualitative research. The subjects of this research are English teachers who implement the problem based learning model. Data collection techniques use observation, interviews and documentation. Data analysis uses the Miles and Huberman model, namely data collection, data reduction, data presentation and conclusions. The result of this study is that it was found that English teachers at the boarding school ashhabul yamin lasi have used five steps in implementing the problem-based learning model. Based on the data collected by the researcher, It can be concluded that all the steps taken by the teacher are in accordance with the steps of each sequence in the problem-based learning model. So, it can be interpreted that the English teacher at the Ashhabul Yamin Lasi Islamic Boarding School is able to apply the problem-based learning model and adapt it to the material being taught. The teacher is able to provide problems or questions according to the abilities of the students. Then the teacher is also able to invite students to be directly involved in the class.